2016
DOI: 10.1007/s11164-016-2430-1
|View full text |Cite
|
Sign up to set email alerts
|

The study of wet etching on GaN surface by potassium hydroxide solution

Abstract: Potassium hydroxide solution was used to etch un-doped GaN grown on the sapphire substrate at 180 and 260°C. We illustrated the etching phenomenon in detail and probed its mechanism in the wet etching process. By multiplying the planar density and the number of dangling bonds on the N atom, we proposed the etching barrier index (EBI) to describe the difficulty degree of each lattice facet. The raking of EBI will be ?cCombining the EBI with SEM results, we thoroughly studied the whole etching process. We confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Surfaces with high density of N dangling bonds possess large repulsion to the hydroxide ions, which stops the crystallographic etching at such surface [29]. The density of N dangling bonds on different GaN lattice planes can be ranked as follows: (0001) plane > (1-210) plane > (10-10) plane > (000-1) plane [30]. Thus, the (0001) plane and (1-210) plane have larger repulsion force to the hydroxide ions, and the TMAH etching did not proceed on the top surface and the sidewall along [10-10] direction under our experiment condition.…”
Section: Resultsmentioning
confidence: 99%
“…Surfaces with high density of N dangling bonds possess large repulsion to the hydroxide ions, which stops the crystallographic etching at such surface [29]. The density of N dangling bonds on different GaN lattice planes can be ranked as follows: (0001) plane > (1-210) plane > (10-10) plane > (000-1) plane [30]. Thus, the (0001) plane and (1-210) plane have larger repulsion force to the hydroxide ions, and the TMAH etching did not proceed on the top surface and the sidewall along [10-10] direction under our experiment condition.…”
Section: Resultsmentioning
confidence: 99%
“…in ref. 30 to describe the etching resistivity of each GaN plane in alkaline etching solution. The higher the EBI of the plane is, the more difficult the etching of the plane would be.…”
Section: Resultsmentioning
confidence: 99%
“…Without the aid of UV light irradiation or bias voltage, the wet etching only selectively occurs at semi-polar and non-polar planes of GaN, which would not prohibit the hydroxide ions from accessing the Ga atom [22,23,24]. It was also reported that the wet etching rate of GaN is dependent on the crystallographic planes of GaN [25,26,27]. Thus, the anisotropic wet etching of GaN generally leads to peculiar textures at different surfaces, such as trigonal prisms and hexagonal pyramids, by exposing specific crystallographic planes [21,28,29].…”
Section: Introductionmentioning
confidence: 99%